Resolución quirúrgica del conducto arterioso persistente en cachorros caninos de uno a seis meses - Llanos Ugsha, Daniel Francisco (2021)
The objective of this work is to carry out a bibliographic review on the surgical resolution of patent ductus arteriosus (PDA). This is the most common congenital heart disease in dogs and generally causes heart failure and death unless corrected at a young age. Factors associated with long-term survival in dogs treated surgically for patent ductus arteriosus are related to age, breed, sex, body weight, clinical examination findings, type and duration of medical treatment, results of chest radiography, echocardiography and surgical and postoperative complications. Technological advances in diagnostic tools offer more and more possibilities for the diagnosis and treatment of congenital heart disease, especially in CAP, which is the central theme of this review. The procedure for surgical correction of CAP by ligation is described and the procedure for correction of CAP by catheterization is mentioned. Finally, the postoperative phase and its possible complications are described.